Simulation and Numerical Analysis of Energy-and-Ecological Compatibility of Indoor Plant Lighting - S. A. Rakutko; E. N. Rakutko (Сельскохозяйственные машины и технологии, 2019)
To develop the theory and practice of operation procedures in a greenhouse, a mathematical model of indoor plant lighting is required. (Research purpose) Development of a simulation and analysis technique of energy-and-ecological compatibility of indoor plant lighting. (Materials and methods) The authors experimentally verifi ed the proposed technique for the indoor plant lighting of tomato seedlings grown under laboratory conditions with controlled environmental parameters. An irradiator consisting of a LED matrix with secondary optics and a driver was used. The photoperiod amounted to 16 hours. The experiment was completed for 46 days. The technique includes an analysis of the energy conversion effi ciency at various stages in the blocks of the artifi cial bioenergy system of indoor plant lighting (ABES): a source of electrical power; a radiation source; an optical part; spatial fl ow distribution; surface fl ow distribution; and a plant. The authors proposed formulas for calculating the energy consumption of each ABES unit. It was revealed that for the estimated values of the energy consumption of ABES blocks taken according to expert estimates, the total energy consumption accounts for 0.32-2.27 megajoule per one gramme of wet weight of a plant, i.e. diff ers by almost an order of magnitude, depending on the specifi c implementation of the lighting technology. It is shown that optimization cannot be limited by consistent selection of an option with the lowest value of energy consumption at each stage, but requires fi nding the optimal route on the graph of options. (Results and discussion) For the experimental conditions, the total energy consumption of ABES was 3.77 megajoule per one gramme of the wet weight of a plant. The low effi ciency was caused by the unsatisfactory effi ciency of the LED matrix and the low productivity of the plant photosynthesis. (Conclusions) The developed technique for modeling and analyzing the energy-and-ecological compatibility of indoor plant lighting allowed assessing possible energy saving at each stage of energy and substance conversion in indoor plant lighting. Theoretically, possible reduction of losses in the source of electrical power is 22 percent, in the optical part – 14 percent; in spatial fl ow distribution – 16 percent; in surface fl ow distribution – 10 percent. Possible increasing of the lighting source effi ciency depends on the achieved level of technology, which currently provides an output of 2.5 micromole per joule and more. To increase the productivity of indoor plant lighting, it is necessary to precisely match the parameters of the lighting mode and the requirements of plants.